Adherence to a healthy lifestyle in relation to colorectal cancer incidence and all‐cause mortality after endoscopic polypectomy: A prospective study in three U.S. cohorts. Issue 9 (6th July 2022) - Wang, Liang; Knudsen, Markus D.; Lo, Chun‐Han; Wang, Kai; He, Mingming; Polychronidis, Georgios; Hang, Dong; He, Xiaosheng; Zhong, Rong; Wu, Kana; Chan, Andrew T.; Ogino, Shuji; et al.
Abstract: It remains unknown whether maintenance of a healthy lifestyle after endoscopic polypectomy could still confer benefit for colorectal cancer (CRC) incidence and mortality. In this study, we defined a healthy lifestyle score based on body mass index, smoking, physical activity, alcohol consumption and diet (range, 0‐5). We used Cox proportional hazards regression to estimate the hazard ratios (HRs) for the associations of healthy lifestyle score and individual lifestyle factors with CRC incidence and all‐cause mortality. During a median of 10 years of follow‐up of 24 668 participants who underwent endoscopic polypectomy, we documented 161 CRC cases and 4857 all‐cause deaths. A higher healthy lifestyle score after endoscopic polypectomy was associated with lower risk of CRC and all‐cause mortality. Compared with individuals with 0 to 1 healthy lifestyle factors, those with 2, 3 and 4 to 5 healthy lifestyle factors had a HR for CRC risk of 0.86 (95% confidence interval [CI], 0.60‐1.24), 0.73 (95% CI, 0.47‐1.14) and 0.52 (95% CI, 0.27‐1.01), respectively ( P trend  = .03). The corresponding HR (95% CI) for all‐cause mortality was 0.83 (95% CI, 0.76‐0.90), 0.63 (95% CI, 0.56‐0.70) and 0.56 (95% CI, 0.48‐0.65), respectively ( P trend  < .0001). In the joint analysis of pre‐ and postpolypectomy periods, patients with a healthy postpolypectomy lifestyle had a lower incidence of CRC regardless of their prepolypectomy exposure, whereas those with a healthy lifestyle in both periods had a lower mortality than those with an unhealthy lifestyle in either period. In conclusion, adherence to a healthy lifestyle after polypectomy may confer significant benefit for CRC prevention and reduction in all‐cause mortality. Abstract : What's new? Lifestyle modifications play an essential role in colorectal cancer prevention. However, it remains unclear whether this prevention strategy remains beneficial following polyp removal. This prospective study in patients who underwent colorectal endoscopic polypectomy indicates that greater adherence to an overall healthy lifestyle consisting of nonsmoking, a high‐quality diet, moderate‐to‐vigorous physical activity, a healthy body mass index and none‐to‐moderation alcohol consumption is associated with lower risk of colorectal cancer and all‐cause mortality. These results suggest that lifestyle modifications remain important for colorectal cancer prevention and health improvement even among patients who have developed and been resected with precursor lesions.